Differential plasma microRNAs expression in juvenile idiopathic arthritis. Issue 2 (3rd March 2016) - Ma, Xiaolin; Wu, Fengqi; Xin, Le; Su, Gaixiu; He, Feng; Yang, Yang; Sun, Juan; Liu, Zhewei
Abstract : Objectives. To identify potential novel biomarkers for juvenile idiopathic arthritis (JIA), we evaluated the correlation between plasma expression levels of specific miRNAs and disease characteristics of JIA. Methods. Differentially expressed miRNAs in JIA plasma were identified by microarray analysis. Five candidate plasma miRNAs with differential expression were further evaluated by qRT-PCR. The correlation between the expression of candidate plasma miRNAs and clinical parameters of JIA patients was assessed. Results. The expression of miR-16, miR-146a, and miR-223 was higher, and miR-132 was lower, in the plasma of JIA patients as compared with healthy subjects and juvenile ankylosing spondylitis patients ( p < 0.05). Plasma miR-16 concentrations were considerably higher for polyarticular JIA patients than oligoarticular JIA patients and correlated with the juvenile arthritis magnetic resonance imaging scores for the hip and plasma interleukin-6 or IL-6 levels. Additionally, miR-146a levels correlated directly with the Juvenile Arthritis Disease Activity Scores in 27 joints, the swollen joint count, the limited joint count, and the juvenile arthritis magnetic resonance imaging scores for the hip, but correlated inversely with plasma tumor necrosis factor-α or TNF-α levels. Conclusions. This study demonstrates that the expression of plasma miRNAs correlates with JIA disease and suggests that plasma miR-16 and miR-146a have potential novel value for JIA diagnosis.